1985
DOI: 10.1007/bf01186442
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency of hyperbaric oxygenation therapy in early forms of cerebrovascular disorders

Abstract: We present results of the assessment of the efficiency of hyperbaric oxygenation therapy in 104 patients with cerebrovascular diseases. Of these patients 32 had chronic cerebrovascular insufficiency and 72 showed transient disturbances of the cerebral circulation. A good effect was noted in 74 patients, a satisfactory one in 22, and a doubtful one in 8 patients. It is concluded from clinical, electrophysiological, psychophysiological, biochemical, and ophthalmoscopic examinations that hyperbaric oxygenation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…5 - 16 In about half of the cases, improvement in status has been claimed on clinical or electroencephalographic grounds, although the observations were uncontrolled. No prospective trial of HBO treatment has been reported.…”
mentioning
confidence: 99%
“…5 - 16 In about half of the cases, improvement in status has been claimed on clinical or electroencephalographic grounds, although the observations were uncontrolled. No prospective trial of HBO treatment has been reported.…”
mentioning
confidence: 99%
“…These searches failed to return any previously unidentified studies warranting inclusion in the full review. Two papers by Heyman et al [28] and Akimov et al [37] were reviewed by the Chair.…”
Section: Secondary Searchesmentioning
confidence: 99%
“…The patients suffered from a wide array of disorders. [37] Description: This paper was originally published in Russian in 1979. The authors comment on the effects of hyperbaric oxygen given periodically over 3 years to 104 patients with 'cerebrovascular' disorders.…”
Section: Papermentioning
confidence: 99%